2020
DOI: 10.1167/iovs.61.12.5
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Annular Tendon (Annulus of Zinn) as a Common Origin of the Extraocular Rectus Muscles: 2. Embryological Basis of Extraocular Muscles Anomalies

Abstract: PURPOSE. Many reports have described anomalous connections of the superior rectus (SR) with other extraocular rectus muscles, in which additional heads of the other three rectus muscles likely provided the connections. We examined how these connections are established during fetal development. METHODS. We analyzed paraffin-embedded horizontal sections from 25 late-stage fetuses. Horizontal sections are best suited for understanding the mediolateral relationships of muscle origins. RESULTS. We confirmed a commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The results of this study suggested differences in the origins of the extraocular muscles, with the superior rectus and obliquus superior originating from the OS‐sup and the inferior and medial recti from the OSpost. This result was consistent with our previous studies in late‐term fetuses and adults (Kim et al, 2020; Naito et al, 2019), which showed that the superior obliquus, levator palpebrae superioris, and superior rectus originated from the upper margin of the optic canal, whereas the other three recti arose from the medial wall of the fetal large orbital fissure (i.e., the OSpost). After birth, these origins may be connected or bundled by the future tendinous annulus.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of this study suggested differences in the origins of the extraocular muscles, with the superior rectus and obliquus superior originating from the OS‐sup and the inferior and medial recti from the OSpost. This result was consistent with our previous studies in late‐term fetuses and adults (Kim et al, 2020; Naito et al, 2019), which showed that the superior obliquus, levator palpebrae superioris, and superior rectus originated from the upper margin of the optic canal, whereas the other three recti arose from the medial wall of the fetal large orbital fissure (i.e., the OSpost). After birth, these origins may be connected or bundled by the future tendinous annulus.…”
Section: Discussionsupporting
confidence: 93%
“…Paraffin‐embedded sagittal sections were obtained from 25 embryos and fetuses of approximate GA 6–34 weeks and CRL 12–295 mm. Because sagittal sections show topographical anatomy better than horizontal sections, sagittal sections of the sphenoid have been used to assess the anatomy of the developing cavernous sinus (Sato et al, 2020) and extraocular rectus muscles (Kim et al, 2020; Naito et al, 2019). The specimens were categorized into four groups by age and size, with Group 1 consisting of four embryos of GA 6 weeks and CRL 12–15 mm, Group 2 of six early fetuses of GA 7–8 weeks and CRL 24–35 mm, Group 3 of eight midterm fetuses of GA 12–15 weeks and CRL 71–115 mm, and Group 4 of seven late‐term fetuses of GA 25–34 weeks and CRL 200–295 mm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dural sheath has recently been recognized to be bilaminar from a biomechanical point of view (Shin et al, 2020), but no studies have demonstrated that both the meningeal and periosteal laminae of the dura continue to the dural sheath of the optic nerve. Our recent studies on the bony origin of the extraocular rectus muscles (Kim et al, 2020;Naito et al, 2019) demonstrated that the periosteum of the sphenoid is continuous with the dural sheath of the intraorbital optic nerve.…”
mentioning
confidence: 99%